Building a fully digital controller with Altera Cyclone FPGA and Nios processor for induction heating application - Jairo Villamizar; Vamsi Borra; Frank Li (Discover Electronics)
Abstract This paper presents the development of a fully digital controller for induction heating machines, capable of delivering up to 50 kW and operating within a frequency range of 100 kHz to 500 kHz. The controller employs a novel approach to phaseshift calculation between voltage and current using successive high-speed subtractions, allowing for the calculation of a new angle in just a few microseconds and ensuring precise power regulation by adjusting frequency. To protect the inverter, the controller effectively prevents operation in the capacitive region, a critical requirement for safeguarding system integrity. Performance evaluations demonstrate minimal phase-shift errors, ensuring stable and efficient operation within the required safety margins. The architecture, built on Intel Altera Cyclone III FPGA devices, offers scalability and adaptability for implementing various modulation techniques.